2019
DOI: 10.1111/pai.13031
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of APT for food allergy in children: a systematic review and meta‐analysis

Abstract: Background The role of atopy patch test (APT) in the diagnosis of food allergy (FA) remains largely controversial. In our meta‐analysis, we aimed to evaluate the accuracy of APT for diagnosing FA in children. Methods Pubmed, Embase and Cochrane Library were searched for studies regarding the diagnostic value of APT for FA in children compared to oral food challenge (double‐blind placebo‐controlled food challenge and/or open food challenge). The last search was conducted on November 11, 2017. Two reviewers inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
(222 reference statements)
1
17
1
5
Order By: Relevance
“…The second systematic review [112] showed a good quality assessment. The authors indicated the PICO research approach and criteria for selecting eligible studies, and they included estimates of likely bias to give quality weights.…”
Section: Accuracy Of Atopy Patch Test Compared To Ofcmentioning
confidence: 96%
See 1 more Smart Citation
“…The second systematic review [112] showed a good quality assessment. The authors indicated the PICO research approach and criteria for selecting eligible studies, and they included estimates of likely bias to give quality weights.…”
Section: Accuracy Of Atopy Patch Test Compared To Ofcmentioning
confidence: 96%
“…A total of 56 articles were identified by the literature search. Two of these were systematic reviews [112,113], and one a meta-analysis. As this kind of study is considered to be the highest quality evidence, we have provided an overview of the research published since then.…”
Section: Accuracy Of Atopy Patch Test Compared To Ofcmentioning
confidence: 99%
“…In a systematic review of studies using APT vs double‐blind placebo‐controlled or open‐food challenges, APT was more useful in patients with AD and gastrointestinal symptoms than in those suspected of any type of food allergy as a whole. The pooled sensitivity in AD was 53.60% (95% CI: 51.10%‐56.00%) and the specificity was 88.60% (95% CI: 87.10%‐90.00%) …”
Section: Introductionmentioning
confidence: 99%
“…The pooled sensitivity in AD was 53.60% (95% CI: 51.10%-56.00%) and the specificity was 88.60% (95% CI: 87.10%-90.00%). 9 We hypothesized that because cutaneous sensitization is less durable in atopic patients, APT would be less commonly positive than tests for immediate-type hypersensitivity. We retrospectively reviewed pediatric patients we had tested with APT who also had results for SPT or sIgE available to the same antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Cabe resaltar que la prueba de parche puede tener utilidad en otras alergias alimentarias no mediadas por IgE, como en los pacientes con alergia alimentaria y dermatitis atópica; no obstante, la falta de estandarización dificulta la interpretación sistemática de los resultados. 6 Consideramos que el reporte de González Cruz et al es útil para informar la necesidad de mantener la sospecha diagnóstica de SEIPA en casos como el descrito, sin embargo, con base en los estudios clínicos disponibles y la evidencia reciente de su inmunopatología, la prueba de parche en su forma actual no debe ser considerada para la corroboración de SEIPA o como método rutinario de su diagnóstico. De igual forma, consideramos que el estudio de las enfermedades gastrointestinales inmunes, como el SEIPA, es el escenario ideal para un enfoque traslacional que propicie el intercambio académico entre la clínica y el laboratorio.…”
unclassified